2013
DOI: 10.1155/2013/106516
|View full text |Cite
|
Sign up to set email alerts
|

A Compact Single-Feed Circularly Polarized Microstrip Antenna with Symmetric and Wide-Beamwidth Radiation Pattern

Abstract: A compact single-feed circularly polarized microstrip antenna is proposed to achieve symmetric radiation pattern over a wide range of observation angles. In order to reduce the radiation aperture and consequently broaden the circular polarization (CP) and the half power beamwidth (HPBW) of the antenna, a partially etched superstrate and a conducting cavity are employed in the design. Further, reasonable axial ratio (AR) and impedance bandwidths are realized within the compact structure by using a simple series… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 11 publications
0
21
0
Order By: Relevance
“…This low value comes from the use of truncated corners. Sharma [1] showed that this type of antenna could not provide a large bandwidth at the axial ratio. Figure 7 shows the 3D radiation pattern of the proposed antenna for the resonant frequency 2.45GHz.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This low value comes from the use of truncated corners. Sharma [1] showed that this type of antenna could not provide a large bandwidth at the axial ratio. Figure 7 shows the 3D radiation pattern of the proposed antenna for the resonant frequency 2.45GHz.…”
Section: Resultsmentioning
confidence: 99%
“…Either by cutting two of its corners or by making a diagonal opening in its metallization. These three topologies have been studied by Sharma et al [1].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The wider adoption of CP technology is attributable to alignment variability (i.e., horizontal, vertical, and diagonal) of the receiving antenna with reliable performance [1]. Previous research has experimented with diverse antenna structures to produce circular polarization (CP) [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…However, the complexity of two feeding ports can be adjusted into one feeding port with an unequally split feeding structure [6,7], modifying the feeding structure into an S-shape [8], or using sequential rotation feeding structure [9] instead. Nevertheless, instead of changing the feeding structure of the antenna, there are many different methods that could also result in the antenna being circularly polarized such as the modification of the slot structure using various shape slits [10], adding a pair of inverted L [11], implementing truncated corners [12], introducing a parasitic patch [13,14], placing a parasitic unequal linear slots [15], T-shaped slot [16], or S-shaped slot [17], using two-diode controlled slot [18], and changing the main slot structure into a set of small square slots with multiple rectangular arms [19].…”
Section: Introductionmentioning
confidence: 99%